A review of research on environmental awareness based on bibliometric analysis: initiation, progress and future - Karacaoğlu, Ömer Cem; Aynur Yılmaz, Aysun; Özkaya, Abdulkadir (International Journal of Evaluation and Research in Education (IJERE), 2025)
“Environmental awareness” (EA) is an important factor in helping to eliminate environmental problems and mobilizing individuals and communities. This study addresses the vast literature on EA by presenting a bibliometric analysis of 564 EA studies in the social science citation index (SSCI) in the Web of Science (WoS) database. The study started with a query of EA-related publications in the WoS database and included an exploration stage covering topics such as distribution by years, most cited journals, publishing countries and active universities. The second stage involved the visualization of EA research on keywords through analysis and visual maps using Biblioshiny and VOSviewer software. The third stage involves naming the constructs and identifying their main characteristics. The analysis of keywords and the cluster names made in the light of these words provide a broad perspective of EA research. The final stage, validation, aims to determine the validity of the constructs based on the relationships between concepts. The overall results of the study show that EA research is influential across the world and is shaped around various themes. The identified themes guide future research and policymaking by emphasizing environmental education, sustainability, early childhood education, active learning, and interdisciplinary collaboration.